United Republic of Tanzania : Poverty Reduction Strategy Paper; Annual Implementation Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2008)
A sound fiscal stance has been the bedrock for Tanzania's macroeconomic stability in recent years. Impressive increases in government revenues, together with substantial donor support, allowed for strong increases in government spending, without excessive recourse to domestic borrowing that could create pressures on monetary policy or crowd out private sector borrowing. To ensure a smooth implementation of the budget, further work is required to strengthen cash management. In addition, local government budget planning and execution remains weak and needs to be strengthened.